National discourses on women's empowerment in Bangladesh: continuities and change - Hossain, Naomi; Nazneen, Sohela; Sultan, Maheen (BRAC University, 2011)
As Bangladesh turns 40, improvements in women’s wellbeing and increased agency are claimed to be some of the most significant gains in the postindependence era. Various economic and social development indicators show that in the last 20 years, Bangladesh, a poor, Muslim‐majority country in the classic patriarchal belt, has made substantial progress in increasing women’s access to education and healthcare (including increasing life‐expectancy), and in improving women’s participation in the labour force. The actors implementing such programmes and policies and claiming to promote women’s empowerment are numerous, and they occupy a significant position within national political traditions and development discourses. In the 1970s and 1980s development ideas around women’s empowerment in Bangladesh were influenced by an overtly instrumentalist logic within the international donor sphere. This led to the women’s empowerment agenda being perceived as a donor driven project, which overlooks how domestic actors such as political parties, women’s organizations and national NGOs have influenced thinking and action around it. This paper explores how these perceptions and narratives around women’s empowerment have evolved in Bangladesh from 2000 to date. It studies the concepts of women’s empowerment in public discourse and reviews the meanings and uses of the term by selected women’s organizations, donor agencies, political parties and development NGOs. By reviewing the publicly available documents of these organizations, the paper analyses the multiple discourses on women’s empowerment, showing the different concepts associated with it and how notions such as power, domains and processes of empowerment are understood by these actors. It also highlights how these different discourses have influenced each other and where they have diverged, with an emphasis on what these divergences mean in terms of advancing women’s interests in Bangladesh.